2021
DOI: 10.9734/jpri/2021/v33i32b31747
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Needle Stick Injury among Surgeons

Abstract: Aim: To find out the prevalence of needle stick injury, its reporting system and the reasons behind it. Study design: Descriptive cross-sectional Place and duration of study: Study was conducted at Jinnah post-graduate medical center (JPMC) Karachi during the period of March to September 2019 Methodology: A self-designed, self-explanatory questionnaire was used, consisting of two parts, the first part was about demographic information while second part is for information related to needle sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…A study of nurses in the United States showed that they are at a greater risk of NSIs by having more shift and working hours. [ 5 ] In our study, technician and laboratory staff who were defined as the other group had the highest incidence of NSI in contrast with the nurses; supervised training of infection control department could be an effective way in the monitoring of nurses which cause the reduction of NSI. One study in Thailand showed that training without practice, lack of awareness, insufficient staff, not using protective equipment, and haste could result in NSI.…”
Section: Discussionmentioning
confidence: 82%
“…A study of nurses in the United States showed that they are at a greater risk of NSIs by having more shift and working hours. [ 5 ] In our study, technician and laboratory staff who were defined as the other group had the highest incidence of NSI in contrast with the nurses; supervised training of infection control department could be an effective way in the monitoring of nurses which cause the reduction of NSI. One study in Thailand showed that training without practice, lack of awareness, insufficient staff, not using protective equipment, and haste could result in NSI.…”
Section: Discussionmentioning
confidence: 82%